Pendugaan Umur Simpan Produk Granula Ubi Kayu Menggunakan Model Isoterm Sorpsi Air (Shelflife Prediction of Cassava Granule using Moisture Sorption Isotherm Model) - Sugiyono Sugiyono; Hoerip Satyagraha; Wiwiek Joelijani; Elvira Syamsir (JURNAL PANGAN, 2012)
Penelitian ini bertujuan untuk menentukan umur simpan produk granula ubi kayu dengan menggunakan model isoterm sorpsi air dan pendekatan kadar air kritis. Kurva isoterm sorpsi produk granula ubi kayu berbentuk sigmoid. Uji ketepatan model persamaan kurva isoterm sorpsi menunjukkan bahwa model Henderson paling tepat menggambarkan kurva isoterm sorpsi granula ubi kayu. Granula ubi kayu memiliki kadar air awal 4,92 persen (bk) dan kadar air kritis 15,24 persen (bk). Hasil perhitungan menunjukkan bahwa granula ubi kayu yang dikemas dalam LDPE, MDPE dan PP pada RH 95 persen mempunyai umur simpan masing-masing 256 hari (8.5 bulan), 427 hari (14 bulan), dan 693 hari (23 bulan).The objective of this research was to predict the shelf life of cassava granule using moisturesorption isotherm model based on critical moisture approach. The sorption isotherm curve of the product showed to be sigmoidal. The Herderson model was found to be the best-fit for the product The product had an initial moisture content of 4.92 percents (db) dan a critical moisture content of 15.2 4percents (db). Based on calculations, the shelf life of cassava granules packaged in LDPE, MDPE, PP and stored at relative humidity of 95 percents, had shelf lives of 256 days (8.5 months), 427 days (14 months), and 693 days (23 months) respectively